Antibiotic-Related Adverse Drug Reactions in Patients Treated on the Dermatology Ward of Medical University of Gdańsk - Ewa Maria Sokolewicz; Martyna Rogowska; Miłosz Lewandowski; Monika Puchowska; Dorota Piechota; Wioletta Barańska-Rybak (MDPI AG, 2021)
Adverse drug reactions (ADRs) are unexpected reactions to a medication administered in a correct way at a standard dose. Drug-induced skin reactions account for 60-70% of all ADRs. The aim of the study is to determine the prevalence of antibiotic-related dermatological ADR in patients treated in the department of Dermatology, Venerology and Allergology of the University Clinical Center in Gdańsk, Poland, in the years 2004-2021. A retrospective analysis of patients' medical files was conducted in order to identify cases of ADR connected with the use of antibiotics, yielding 84 cases. The most common group of antibiotics were β-lactam, causing ADR in 47 patients. β-lactam antibiotics in our study included amoxicillin, alone and combined with clavulanic acid, and cephalosporins, affecting 22, 18 and 7 patients, respectively. In conclusion, β-lactam antibiotics showed the highest prevalence among antibiotic-induced skin reactions. They accounted for 15% of cases of all dermatological drug reactions and 55% of those caused by antibiotics. Especially amoxicillin, prescribed as a single drug or in combination with clavulanic acid, was commonly the culprit. Due to its wide use in the hospital and outpatient clinic, these adverse reactions have to be kept in mind by both hospital staff and general practitioners.